Potassium Chloride Sustained Release Dosing Pathway in an Academic Medical Center. Issue 4 (December 2017) - Cook, Bryan M.; Carter, Danielle M.; Dell'Orfano, Heather; Matta, Lina
Abstract : Potassium supplementation can be administered intravenously or orally with either immediate release or sustained release formulations. Sustained release potassium chloride allows for delayed absorption and peak effects. In the inpatient setting, it is important to monitor and prevent both hypokalemia and hyperkalemia. Our tertiary-care academic hospital created a clinical pathway for sustained release potassium chloride supplementation in the inpatient population. Our clinical pathway for sustained release potassium chloride creates dosing restrictions designed to prevent hyperkalemia, while allowing exceptions for patients with high requirements.